2017
DOI: 10.18483/ijsci.1400
|View full text |Cite
|
Sign up to set email alerts
|

Elemental Assessment in Economically Important Cirrhinus Mrigala and Labeo Rohita Fish Species Captured from Indus River at Guddu Barrage, Sindh, Pakistan

Abstract: Abstract:This study aimed to investigate the level of trace and toxic elements (Fe, Ni, Cu, Co, Mn, Zn, Cr, Cd and Pb) in Rohu (labeo rohita) and Mrigala (cirrhinus mrigala) fish species of Indus River at the region of Guddu Barrage, Sindh, Pakistan. The fish samples were collected and processed in the Laboratories of Institute of Chemistry, Shah Abdul Latif University, Khairpur, Sindh, for elemental analysis in gill, muscle and liver of both fish species using Atomic Absorption Spectrophotometer. Results re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Jakhrani et al studied bioaccumulation of heavy metals and traced elements (iron, zinc, copper, manganese, nickel, cadmium, and chromium) in three different fish species viz., Catla catla, Cirrhinus mirigala and Labeo rohita caught from ponds in district Kashmore, Pakistan. The results showed that the bioaccumulation of heavy metals and trace elements was higher in gills than liver and muscles (Jakhrani et al, 2019). Iqbal also reported a similar bioaccumulation trend as in the present study, i.e., highest in the gills and lowest in the muscles when he carried out the studies in two fish species Labeo rohita and Wallago attu caught from Taunsa barrage of the Indus river in Pakistan (Iqbal et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…Jakhrani et al studied bioaccumulation of heavy metals and traced elements (iron, zinc, copper, manganese, nickel, cadmium, and chromium) in three different fish species viz., Catla catla, Cirrhinus mirigala and Labeo rohita caught from ponds in district Kashmore, Pakistan. The results showed that the bioaccumulation of heavy metals and trace elements was higher in gills than liver and muscles (Jakhrani et al, 2019). Iqbal also reported a similar bioaccumulation trend as in the present study, i.e., highest in the gills and lowest in the muscles when he carried out the studies in two fish species Labeo rohita and Wallago attu caught from Taunsa barrage of the Indus river in Pakistan (Iqbal et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…Equations (5) and (6) represent the Stefan-Boltzmann law. Linearisation of these two equations is carried out here according to the procedure described in [7].…”
Section: Model Descriptionmentioning
confidence: 99%
“…After solving for TPV, the values of hrad,f and hrad,b in equations (5) and (6) may be reestimated, respectively, and then may be solved for TPV again. A nearly exact solution may be obtained after 5-6 iterations.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Merciai et al (2014) observed higher concentrations of Fe than Zn in the muscles of the fish they studied. Similarly, Jakhrani et al (2017) had reported higher levels of Fe than Zn in homogeneous and dried samples of liver, gills and muscles of L. rohita and Cirrhinus mrigala. Mannan et al (2018) studied the bioaccumulation of heavy metals in fish before and after feeding with synthetic feed for six months and reported higher levels of Cu, Cr, Cd, Pb, Fe and Zn.…”
Section: Multiple Regression Analysis (Mra)mentioning
confidence: 89%